2004
DOI: 10.1124/dmd.32.8.884
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the in Vitro Intrinsic Clearance of the Slowly Metabolized Compound Tolbutamide Determined in Sandwich-Cultured Rat Hepatocytes

Abstract: ABSTRACT:An alternative approach is introduced in determining the in vitro intrinsic clearance of slowly metabolized compounds. The longterm sandwich rat hepatocyte culture was exploited, allowing for sufficient substrate depletion to obtain a reliable clearance estimation; in its physiology, it resembles the in vivo liver, thus allowing in vivo extrapolation of the in vitro clearance value. Substrate depletion of tolbutamide and the formation of its metabolites hydroxytolbutamide and carboxytolbutamide were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
(42 reference statements)
3
32
0
Order By: Relevance
“…The in-vivo CL bile -for the two other compounds were underpredicted by 2.2-(mebrofenin) and 4.6-fold (sesamibi) (despite the neglect of blood component binding). This suggests that the in-vitro transporter activity in these experiments was quite low (down-regulated) and/or that there had been diffusion limitations (previously shown for the sandwich-cultured hepatocyte model; Treijtel et al 2004). ).…”
Section: Predictions In Manmentioning
confidence: 94%
See 1 more Smart Citation
“…The in-vivo CL bile -for the two other compounds were underpredicted by 2.2-(mebrofenin) and 4.6-fold (sesamibi) (despite the neglect of blood component binding). This suggests that the in-vitro transporter activity in these experiments was quite low (down-regulated) and/or that there had been diffusion limitations (previously shown for the sandwich-cultured hepatocyte model; Treijtel et al 2004). ).…”
Section: Predictions In Manmentioning
confidence: 94%
“…The sandwich-cultured hepatocyte method has other apparent advantages over suspended hepatocytes (for studies on bile transport and CL): intact canalicular networks are developed; protein expression and function are retained; and metabolizing capacity decreases more slowly (Liu et al 1999;Chandra & Brouwer 2004;Griffin & Houston 2005). A proposed drawback with this method is that drug diffusion in the collagen layers may affect the metabolic and transport rates (Treijtel et al 2004).…”
Section: Predictions From Animal Datamentioning
confidence: 99%
“…Furthermore, by addition of serum, other groups have demonstrated an increased prediction accuracy (Blanchard et al, 2006;Chao et al, 2009), assuming a protein-mediated drug uptake or an improved simulation of protein binding/uptake/ metabolism interplay (Hallifax and Houston, 2012;Poulin et al, 2012). To explain the apparent discrepancy of our results, we considered an extensive human serum albumin (HSA) production by cultured UHH as possibility leading to an increased protein content in the incubation matrix, in addition to the Matrigel protein overlay (0.18 mg/mL) contributing to nonspecific binding, or even acting as an additional diffusion barrier (Treijtel et al, 2004). However, secretion of HSA has recently been shown to be comparable between UHH and PHH (Levy et al, 2015), thereby regarded as unlikely to account for the observed discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the hepatocyte relay method (Di et al, 2012) showed successful CL int predictions for low and intermediate CL drugs by sequential short incubations in suspended hepatocytes. Several reports suggest plated hepatocytes to have advantages over suspensions for CL int determinations of low turnover compounds (Blanchard et al, 2004;Treijtel et al, 2004;Griffin and Houston, 2005;Smith et al, 2012). However, deregulation of gene expression of DMEs after plating is a major drawback of primary hepatic cell cultures (Richert et al, 2006), thus complicating the development of reliable long-term culture models.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report to compare multiple-enzyme metabolism in SCH with that in suspension and the in vivo metabolic pathway. Other researchers have compared individual metabolic enzyme activity between the two methods independently (Kern et al, 1997;Slaus et al, 2001;Lau et al, 2002;Treijtel et al, 2004). SCH is beneficial for the determination of the metabolic intrinsic clearance of slowly metabolizing compounds, because it allows long-term incubation (Treijtel et al, 2004;Treijtel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%